Deregulation and the Current Account - Philipp Harms (Swiss National Bank, Study Center Gerzensee, 2002)
We use a dynamic general-equilibrium model to study how removing barriers to competition in the nontraded goods sector affects the current account of a small open economy. We show that the expansion of the nontraded sector that results from such a "deregulation shock" is associated with an accumulation of foreign assets unless the production of nontraded goods is very capital-intensive. We then investigate whether a measure of domestic deregulation does, in fact, help to explain countries' current account balances in recent decades, and find some empirical support for the model's predictions.
Keywords: F41; D43; F32; 330; International macroeconomics; nontraded goods; current account; deregulation; imperfect competition; Deregulierung; Nicht-handelbare Güter; Unvollkommener Wettbewerb; Kleine offene Volkswirtschaft; Wirtschaftliche Anpassung; Leistungsbilanz; Kaufkraftparität; Reallohn; Theorie